Metabolic symbiosis in cancer: Refocusing the Warburg lens. Issue 5 (6th January 2012) - Nakajima, Erica C.; Van Houten, Bennett
Abstract Using relatively primitive tools in the 1920s, Otto Warburg demonstrated that tumor cells show an increased dependence on glycolysis to meet their energy needs, regardless of whether they were well‐oxygenated or not. High rates of glucose uptake, fueling glycolysis, are now used clinically to identify cancer cells. However, the Warburg effect does not account for the metabolic diversity that has been observed amongst cancer cells nor the influences that might direct such diversity. Modern tools have shown that the oncogenes, variable hypoxia levels, and the utilization of different carbon sources affect tumor evolution. These influences may produce metabolic symbiosis, in which lactate from a hypoxic, glycolytic tumor cell population fuels ATP production in the oxygenated region of a tumor. Lactate, once considered a waste product of glycolysis, is an important metabolite for oxidative phosphorylation in many tissues. While much is known about how muscle and the brain use lactate in oxidative phosphorylation, the contribution of lactate in tumor bioenergetics is less defined. A refocused perspective of cancer metabolism that recognizes metabolic diversity within a tumor offers novel therapeutic targets by which cancer cells may be starved from their fuel sources, and thereby become more sensitive to traditional cancer treatments. © 2012 Wiley Periodicals, Inc.